Effect of Information Framing on Wearing Masks During the COVID-19 Pandemic: Interaction With Social Norms and Information Credibility - Peng, Lihong; Jiang, Hao; Guo, Yi; Hu, Dehua (Frontiers in Public Health, 2022)
Objective: The main objectives of this study were to use the information framing (different expressions of the same issue, e.g., positive messages and negative messages) effect to explore the key factors that influence the public's attitude and intention towards wearing masks and to understand the internal and external factors of intervention on information framing perception. Methods: This study used an online questionnaire survey to explore the influence of demographic characteristics, information framing, social norms, and information credibility on the public's attitude towards masks and their intention to wear them. Results: (1) Information framing had a significant impact on people's attitudes toward masks and their intention to wear them, and the persuasion effect of the gain-framed message was higher than that of the loss-framed message. (2) Gender, income, occupation, educational background, and residence have no significant difference in attitude and intention to wear masks; There was a significant correlation between age and mask wearing (p=0.041<0.05). (3) Social norms affected people's perception of information framing and their attitude towards masks wearing, but only the impact of loss-framed messages on intention was significant. (4) Information framing affected people's perception of information credibility, which had a positive impact on their intention to wear masks; however, information credibility only had a significant impact on attitude towards wearing masks under the gain-framed messages and played an intermediary role. Conclusion: The impact of information framing on people's attitude toward masks and their intention to wear them varies. Individuals involved in the publicity of health information related to this issue should pay attention to the influence of information framing and content on public mask wearing as a means of enhancing public health awareness.